Tackling Hypotheticals in Helminth Genomes. Issue 3 (March 2018) - Palevich, Nikola; Britton, Collette; Kamenetzky, Laura; Mitreva, Makedonka; de Moraes Mourão, Marina; Bennuru, Sasisekhar; Quack, Thomas; Scholte, Larissa Lopes Silva; Tyagi, Rahul; Slatko, Barton E.; ,; ,
Abstract : Advancements in genome sequencing have led to the rapid accumulation of uncharacterized 'hypothetical proteins' in the public databases. Here we provide a community perspective and some best-practice approaches for the accurate functional annotation of uncharacterized genomic sequences.